The Battle on the River Boyne in 1690 (based on the English, the Scottish and the Irish Sourses) - Stankov, Kirill N. (Известия Саратовского университета. Новая серия. Серия: История. Международные отношения, 2023)
The article is devoted to the battle on the river Boyne (July 1, 1690) – one of the largest battles of the War of the League of Augsburg and the largest battle in the history of Ireland. The conflict was caused by a clash between two crowned rivals – James II Stuart, who was overthrown during the “Glorious Revolution” of 1688–1689 in England, and Prince of Orange – statholder of the Netherlands, who seized the British throne and proclaimed himself King William III of Britain. The author of the article sought to draw on materials from both opposing sides, as well as those contemporaries who took a neutral position. On the basis of these sources the ratio of forces of the Jacobites and the Orangists, their preliminary preparation for the general battle and its planning, and finally, the course of the battle itself and its results are studied.